Self-emulsifying drug delivery systems: In vivo evaluation of their potential for oral vaccination - Lupo, Noemi; Tkadlečková, Veronika Novakova; Jelkmann, Max; Laffleur, Flavia; Hetényi, Gergely; Kubová, Kateřina; Bernkop-Schnürch, Andreas (Acta biomaterialia, 2019)
Oral Immunization remains a challenge as antigens are rapidly metabolized in the gastrointestinal tract. In numerous previous studies, Self-emulsifying drug delivery systems (SEDDS) have demonstrated to be a promising tool for oral delivery of biologics. In this study, the potential of SEDDS as vehicle for oral vaccination has been evaluated. At this purpose, the model antigen Bovine serum albumin (BSA) has been incorporated in SEDDS after ion pairing. Squalane and monophosphoryl lipid A (MPLA) were chosen as adjuvants and dissolved in SEDDS containing BSA (SEDDS-BSA-squalane and SEDDS-BSA-MPLA). Formulations were administered orally to BALB/c mice. As control unformulated BSA was administrated orally (BSA-oral) and subcutaneously (BSA-sc). Systemic (anti BSA IgG titre) and mucosal (anti BSA IgA titre) immugenicity of BSA loaded in SEDDS and of unformulated BSA administered orally and subcutaneously was assessed and compared with each other. SEDDS-BSA-squalane and SEDDS-BSA-MPLA induced both higher anti BSA-IgG titre and anti BSA-IgA titre than orally administered unformulated BSA. BSA-sc induced the highest systemic immune response, however, the highest mucosal immune response was achieved via oral administration of SEDDS-BSA-squalane and SEDDS-BSA-MPLA. In general, SEDDS-BSA-MPLA showed the most promising systemic and mucosal immune response. According to these results, SEDDS seems to be a promising carrier for oral delivery of vaccines. STATEMENT OF SIGNIFICANCE: Oral vaccination is still a great challenge, as orally administered antigens are easily degraded in the gastrointestinal (GI) tract by peptidases and proteases. During the last years, self-emulsifying drug delivery systems (SEDDS) consisting of a mixture of oils and surfactants have been developed for the oral administration of hydrophilic macromolecular drugs. In this study, Bovine serum albumin (BSA) was chosen as model antigen and incorporated into self-emulsifying drug delivery systems (SEDDS) after hydrophobic ion pairing. Lipid A from Salmonella Minnesota R595 (MPLA) and squalane were chosen as adjuvants. SEDDS-BSA-MPLA and SEDDS-BSA-squalane were administered orally to mice. SEDDS-BSA-MPLA induced the strongest systemic (anti BSA-IgG titre) and mucosal (anti BSA-IgA titre) immune response. Based on these results, SEDDS are a promising alternative carrier for oral vaccine delivery.
Keywords: vakcinace; imunoglobulin G; Emulsions; Vaccination; Female; myši inbrední BALB C; Administration, Oral; Drug Delivery Systems; lipid A; zvířata; myši; Lipid A; Mice; ženské pohlaví; lékové transportní systémy; emulze; sérový albumin hovězí; Serum Albumin, Bovine; Animals; aplikace orální; Immunoglobulin G; Mice, Inbred BALB C